Mitigating Anxiety Symptoms: Potential of Phenol Compounds in Organic Red Ginger from Simalungun Regency - Dania, Ira Aini; Novziransyah, Nanda; Pangestuti, Dewi; Akbar, Surya; Sari Ayu, Mayang; Lubis, Adi Raja Brando; Ayu, Mayang Sari; Saputra, Donalry Agus (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract— According to WHO (World Health Organization), anxiety disorders affected 266 million people globally in 2019, or 5.3% of the population. As the second most common mental disorder after depression, anxiety impacts 284 million people and significantly contributes to the disease burden worldwide. Meanwhile, regional prevalence rates are 19.2%, 16.2%, 9.0%, and 11.8% in North America, Europe, Africa, and Southeast Asia, with particularly 57.5% and 68.8% rates among pregnant women in Bali (2020) and Semarang (2023), respectively. In this context, ginger (Zingiber officinale), traditionally used for various ailments, contains phenol such as shogaol, zingerone, gingerol, and 6-shogaol, which have antioxidant and anti-inflammatory properties for reducing anxiety. Therefore, this research aims to analyze the phenol contents of ginger using UV-Vis spectrophotometry in the Faculty of Pharmacy, University of North Sumatra. The results show that there is a strong correlation of 0.9794 between gallic acid and phenol content. Additionally, phenol levels are reported with different extraction methods including 43.2653 mgGAE/g (4.326%) with water, 62.7680 mgGAE/g (6.27%) with 70% ethanol, and 129.7456 mgGAE/g (12.97%) with 96% ethanol. The highest phenol content in organic red ginger using 96% ethanol suggests the potential to reduce anxiety by counteracting free radicals.